Containing Tariff Evasion - Clement Anne; Cyril Chalendard; Ana Fernandes; Bob Rijkers; Vincent Vicard (Center for Economic Studies and ifo Institute (CESifo), 2023)
To identify transactions at risk of tariff evasion, this paper matches export transaction data from France with import transaction data from Madagascar using container identifiers. Reporting discrepancies between exporters and importers are prevalent but small, with over two-fifths of importers reporting in a way that increases their tariff liability. Yet, aggregate tariff revenues are 24 percent lower due to discrepancies. These revenue losses are highly concentrated: the top five evaders account for three-quarters of all tariff revenue losses and larger shipments are more at risk of evasion. Tariff enforcement in Madagascar is ineffective and only marginally mitigates revenue losses.
Keywords: F13; D73; H26; 330; tax evasion; mirror statistics; trade; corruption; exporters; importers; tariffs